PENGARUH OLAHRAGA AEROBIK INTENSITAS MODERAT DI RUMAH TERHADAP KUALITAS TIDUR DI MASA PANDEMI COVID - 19 PADA MAHASISWA FK UMSU - PUTRI SARMADANI HASIBUAN; GUSBAKTI RUSIP (LP2MTBM MAKARIOZ, 2021)
The COVID-19 pandemic has caused people to engage in social distancing, namely by staying at home and closing schools.The effects of the COVID-19 pandemic on students lead to online lectures, resulting in excessive use of electronic devicesand resulting in changes to sleep homoestasis. Sleep quality is a feeling of enthusiasm and fitness after awakening fromsleep. Low sleep quality will affect academic activities, behavioral changes and emotional disturbances. A factor that canimprove sleep quality is physical activity, namely by exercising. To determine the effect of moderate intensity aerobicexercise at home on sleep quality during the COVID-19 pandemic in FK UMSU students. This study uses an experimentalmethod with a one group pre and pos test research design with a control group design. Sleep quality was measured usingthe Pittsburgh Sleep Quality Index (PSQI) questionnaire, and measurements were made twice, namely before and afteraerobic exercise intervention. Samples were taken using consecutive sampling technique with a total sample of 36 peopleusing Federer's formula. From the results of this study, all study respondents experienced disturbances in the quality of theirsleep. The results of the Wilcoxon test in the intervention group found p = 0.001, and in the control group it was found p =1,000. Where the moderate intensity aerobic exercise intervention group affected the quality of sleep of FK UMSU studentsduring the COVID-19 pandemic. In the intervention group there was an increase in the quality of sleep in UMSU FK studentsafter being given moderate intensity aerobic exercise. So that moderate intensity aerobic exercise is one of thenonpharmacological methods for people who have sleep quality disturbances.